Working on the edge: remediation work in the UK travel sector. (April 2014) - Ball, Kirstie; Canhoto, Ana; Daniel, Elizabeth; Dibb, Sally; Meadows, Maureen; Spiller, Keith
In response to recent terror attacks, Western governments now involve private sector organizations in national security regimes in key strategic areas such as travel, communication and financial services. The UK's e-Borders programme is one such regime. Its goal is to collect and analyse passport and passenger data from all travellers entering and leaving the UK in advance of travel. Airlines and their supply chains are required to collect data from their customers and transfer it to the UK Border Agency for processing. Using documentary and interview data, this article develops the concept of 'remediation work' to characterize the impact of the regime on travel firms and their employees.